Introduction to Apache Kafka - Shapira, Gwen (O'Reilly Media, 2015)
"Currently one of the hottest projects across the Hadoop ecosystem, Apache Kafka is a distributed, real-time data system that functions in a manner similar to a pub/sub messaging service, but with better througput, built-in partitioning, replication, and fault tolerance. In this video course, host Gwen Shapira from Cloudera shows developers and administrators how to integrate Kafka into a data processing pipeline. You'll start with Kafka basics, walk through code examples of Kafka producers and consumers, and then learn how to integrate Kafka with Hadoop. By the end of this course, you'll be ready to use this service for large-scale log collection and stream processing."--Resource description page.